Exploring the Impact of Perceived Usefulness on Behavioral Intention: The Mediating Role of Trust - Irda, Irda; Dwi Putri, Tyara; Utami, Wiry; Kamela, Ice (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
The purpose of this study is to ascertain how perceived usefulness affects on behavioral intention, with trust acting as a mediating factor in the Shopeepay e-wallet service in Padang. The population in this study are users who intend to use the Shopeepay e-wallet service in the city Padang, with sample size as many as 140 users. Purposive sampling is the procedure used in the sampling approach. The Partial Least Square (PLS) test is used in the data analysis procedure. According to the research's findings, perceived usefulness has a positive effect on behavioral intention. It also found that perceived usefulness has a positive effect on trust. Trust has a positive effect on behavioral intention. The next finding was that trust mediates the effect of perceived usefulness on behavioral intention